Innovation at the Intersection of Clinical Trials and Real‐World Data Science to Advance Patient Care. Issue 5 (16th May 2018) - Swift, Brandon; Jain, Lokesh; White, Craig; Chandrasekaran, Vasu; Bhandari, Aman; Hughes, Dyfrig A.; Jadhav, Pravin R.
Abstract: While efficacy and safety data collected from randomized clinical trials are the evidentiary standard for determining market authorization, this alone may no longer be sufficient to address the needs of key stakeholders (regulators, providers, and payers) and guarantee long‐term success of pharmaceutical products. There is a heightened interest from stakeholders on understanding the use of real‐world evidence (RWE) to substantiate benefit–risk assessment and support the value of a new drug. This review provides an overview of real‐world data (RWD) and related advances in the regulatory framework, and discusses their impact on clinical research and development. A framework for linking drug development decisions with the value proposition of the drug, utilizing pharmacokinetic–pharmacodynamic–pharmacoeconomic models, is introduced. The summary presented here is based on the presentations and discussion at the symposium entitled Innovation at the Intersection of Clinical Trials and Real‐World Data to Advance Patient Care at the American Society for Clinical Pharmacology and Therapeutics (ASCPT) 2017 Annual Meeting.